Strategies to enhance biocompatibility of bone scaffold for tissue engineering applications - S.A.P Sughanthya; M.N.M Ansari; Noor Afeefah Nordin; Ng, Angela Min Hwei (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
Tissue engineering (TE) is a modern approach to improve or restore tissues that has been diseased or damaged by combining the factors in growth signaling and appropriate cells to form compatible biomaterial scaffold. Bone repair has been a major global health challenge in recent decades. Bone transplantation is widely used as an effective clinical treatment for this purpose. However, there are several serious issues with transplantation, including a shortage of autologous bone, immune rejection, the risk of virus transmission with allogeneic bone, and postoperative complications. In recent years, scaffolds for bone tissue engineering have emerged as a promising alternative for bone repair. These scaffolds have porous structures that mimic the extracellular matrix, which can enhance the migration, proliferation, and differentiation of osteoblasts. This process accelerates the repair of bone defects.The usage of bioactive materials has become important tool in tissue engineering and regenerative medicine application as they are to mimic tissues mechanically, chemically, and physically. Polymeric scaffold provides numerous advantageous for tissue engineering since the physicochemical properties such as porosity, pore size, solubility and biocompatibility can be controlled. Therefore, research works were carried out to explore the potential of various materials in producing bone scaffolds in tissue engineering technology. As for both newcomers and experts, this review paper will help them to find information on various types of biomaterials in imparting or enhancing their biological properties such as biocompatibility, bacterial inhibition, tissue regeneration and cell growth, bio inertness, bioactive and resorbability for bone scaffold tissue engineering application.